Generation and Reaction of Functional Alkyllithiums by Using Microreactors and Their Application to Heterotelechelic Polymer Synthesis. Issue 60 (4th September 2019) - Nagaki, Aiichiro; Yamashita, Hiroki; Tsuchihashi, Yuta; Hirose, Katsuyuki; Takumi, Masahiro; Yoshida, Jun‐ichi
Abstract: Invited for the cover of this issue is the group of Aiichiro Nagaki at Kyoto University. The image depicts the reaction in the flow microreactor reported in the paper. Read the full text of the article at 10.1002/chem.201902867 . Abstract : " In this study, we tried to tackle a challenging reaction by developing a new device in which the reaction is performed. By working on an external component instead of the compounds themselves, we successfully developed a much more robust method which can be used for a wide range of similar compounds as well ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13719 ff. (DOI: 10.1002/chem.201902867 ).